2004
DOI: 10.1021/bi049868i
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human Phosphodiesterase 3B:  Atomic Basis for Substrate and Inhibitor Specificity

Abstract: Phosphodiesterases (PDEs) are enzymes that modulate cyclic nucleotide signaling and as such are clinical targets for a range of disorders including congestive heart failure, erectile dysfunction, and inflammation. The PDE3 family comprises two highly homologous subtypes expressed in different tissues, and inhibitors of this family have been shown to increase lipolysis in adipocytes. A specific PDE3B (the lipocyte-localized subtype) inhibitor would be a very useful tool to evaluate the effects of PDE3 inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 29 publications
3
111
0
1
Order By: Relevance
“…6, A and B) with the exception of that for PDE3 (183,327,427); the strong bias in the field is that magnesium occupies Me-2. However, many PDEs have higher affinity for manganese or cobalt than for magnesium in supporting catalytic activity, and for PDE9, V max with manganese is twice that for magnesium (163).…”
Section: Metal Ion Content Coordination and Structural Importancementioning
confidence: 99%
“…6, A and B) with the exception of that for PDE3 (183,327,427); the strong bias in the field is that magnesium occupies Me-2. However, many PDEs have higher affinity for manganese or cobalt than for magnesium in supporting catalytic activity, and for PDE9, V max with manganese is twice that for magnesium (163).…”
Section: Metal Ion Content Coordination and Structural Importancementioning
confidence: 99%
“…3) and has the same topology of folding as do other PDEs (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Two divalent metals were tentatively interpreted as zinc and magnesium for the purpose of structure refinement.…”
Section: Structure and Kinetics Of Pde7mentioning
confidence: 99%
“…The N-terminal fragments of the catalytic domains in the PDE families (130 -157 in PDE7A1) do not have comparable amino acid sequences and vary in their secondary structure elements. Among them, PDE4B, PDE4D, and PDE1B (25,31,38) containing helices H1 and H2 have a similar folding; PDE3B (40) shows only a comparable helix H2; and PDE5 and PDE9 have different secondary and tertiary structures for their N-terminal residues (36,37). The catalytic domain of PDE7A1 resembles PDE4 mostly, and their entire catalytic domains are comparable, as shown by an average difference of 0.93 Å for the superposition of C␣ atoms of PDE7A1 residues 139 -455 on the equivalents of PDE4D2.…”
Section: Structure and Kinetics Of Pde7mentioning
confidence: 99%
“…Tel: +886-4-24730022 ext.11675; Fax: +886-4-23248195; E-mail: lhj@csmu.edu.tw Abbreviations: ROS, reactive oxygen species; STZ, streptozotocin; CTZ, cilostazol; NO, nitric oxide; ECM, extracellular matrix; cAMP, cyclic adenosine monophosphate; cGMP, cyclic guanosine monophosphate; PDE, phosphodiesterase; MDA, malondialdehyde; BUN, blood urea nitrogen; ACR, urine albumin/creatinine ratio; GFR, glomerular filtration rate; PKC, protein kinase C; DAG, diacylglycerol; PI-3K, phosphatidylinositol-3 kinase concentration of cyclic nucleotides changes, the actions of numerous hormones and neurotransmitter signals are mediated for cell growth, differentiation, survival, and inflammation. 14,15) Recent studies have suggested that cAMP and cGMP regulate several signaling pathways involved in the development and progression of renal disease, including mitogenesis, inflammation, and extracellular matrix synthesis. [16][17][18] Cilostazol {6-[4-(1-cyclohexyl-1H-tetrazol-5-yl) butoxy]-3, 4-dihydro-2(1H)-quinolinone} is a specific inhibitor of phosphodiesterase 3 (PDE 3).…”
mentioning
confidence: 99%